The Presenters of Anger Management Programmes : Their Experiences of Working in the Context of Prisons - O'Keefe, Monica (1995)
The study was an exploration of the experiences of eight presenters of anger management programmes in relation to their work in prisons. It was conducted within an interpretive paradigm using a phenomenological framework. From the data analysis, four principal themes emerged. One centred on the impact of the prison environment; another on the work culture of prisons; a third on experiential group processes; and a fourth on personal concerns of the participants. The results suggest the environment and culture of the prison had a strong impact on the presenters personally and had a dominant influence on the way they could work there. Prisons are very restrictive environments where the potential for violence is always present. Therefore it is both challenging and stressful for those who work there. Non-custodial workers need to learn to understand the culture and to adapt to the prison environment to work there effectively. They need training and support to operate within that context, and to have strategies implemented to ensure their personal safety. The study has implications for the selection, training and support of non-custodial prison workers, particularly contract workers. This research is a first step in a possible major research area